(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The first record in Mozambique of Calycomyza lantanae (Frick), leafminer on Lantana camara is referred with remarks on the distribution of the species of Agromyzidae living on Lantana in the world.